Enhancing armored crew safety: a scientometric and scoping review of key trends, challenges, and innovations - Radzi, Elias M.; Hassan, Zuraida; Ismail, Mohd Azril; Abdullah, Khairul Hafezad; Arzahan, Intan Suraya N.; Ishak, Aswalni; Ghalib, Muhammad Hazim A. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: This study presents a comprehensive analysis of the existing literature on armored vehicle crew safety through an integrated scientometric and scoping methodology. Methods: Data sourced from Scopus and Web of Science were employed to analyze a total of 197 documents following preprocessing and the removal of duplicates. Scientometric analysis was conducted utilizing ScientoPy and VOSviewer software to identify publication trends, keyword co-occurrence, and influential academic contributions. Furthermore, a scoping review based on the SPIDER framework was undertaken to synthesize critical insights related to whole-body vibration (WBV), vehicle design, and safety technologies. Results: The findings indicate that the installation of bulletproof armor significantly reduces WBV exposure levels, with reductions ranging from 10% to 20%. These reductions are attributed to modifications in vehicle mass distribution and stiffness. Advanced materials, such as aluminum alloys, were identified as essential for enhancing blast resistance and vibration mitigation. The results emphasize the importance of structural modifications and adaptive technologies, including enhanced suspension systems, in managing WBV and improving overall crew safety. Conclusion: This study establishes a robust foundation for future research, underscoring the necessity for optimized vehicle designs and integrated safety strategies to address the physiological and psychological stressors encountered by armored vehicle crews.